A modified multi-stepped constant current based on gray wolf algorithm for photovoltaics applications - Dagal, Idriss; Akin, Burak; Dari, Yaya Dagal (SPRINGER, 2024)
One of the most known and usable renewable energy is photovoltaic solar energy. Its properties such as recursivity, cleanness, limitlessness, and reliability make it the most useful source of energy. Some undesirable natural (irradiance and temperature) variation affects the photovoltaic solar modules' characteristics. However, photovoltaic PV solar power needs to be monitored accurately, effectively, and efficiently in order to keep the global maximum power point (GMPP) steady. Therefore, this paper presents a modified multi-stepped constant current based on the gray wolf optimization (MMSCC-GWO) algorithm for photovoltaic systems. The proposed technique utilizes a multi-step constant current to the pack of wolves by monitoring the inside and the outside step of the hierarchical wolves. This proposed (MMSCC-GWO) algorithm accurately tracks the maximum power point from the photovoltaic systems under different partial shading conditions (PSCs). A comparative result with other conventional methods is investigated and the simulation results carried out in the MATLAB/Simulink environment reveal that the proposed approach outperforms the existing techniques in terms of efficiency, tracking time, and accuracy.
Keywords: Efficiency; gray wolf optimization algorithm; Multi-stepped constant current; Partial shading; FLOWER POLLINATION ALGORITHM; POWER POINT TRACKING; PV SYSTEMS; OPTIMIZATION; Engineering